Remembering Tiananmen and the Berlin Wall: the elite U.S. press’s anniversary journalism, 1990–2009 - Li, Hongtao and Lee, Chin-Chuan (Media, Culture & Society, 2013)
This article examines how the New York Times and the Washington Post have in the past two decades presented discourses of anniversary journalism to commemorate the Tiananmen Square crackdown and the fall of the Berlin Wall, both of which occurred in 1989 and had global implications. These two events ideologically signified the failure of Communism and the victory of the West. However, they posed different challenges to the U.S.-orchestrated “new world order.” Insofar as the Tiananmen crackdown was remembered as an “unfinished revolution” and fell within the “sphere of legitimated controversy,” the elite U.S. press had greater leeway in presenting the views of elite factions, albeit all within the orbit of “established pluralism.” In contrast, since European integration after the fall of the Berlin Wall was an issue of broad elite consensus, the press constructed its perspectives more closely aligned with those of official foreign policy. Anniversary journalism connects personal reminiscences of distinguished journalists to the dominant narratives. The ideological structure of the elite U.S. press has been highly stable, even though the narratives may appear to shift periodically. The legacy of the anti-Communist frame remains an important constituent of the elite U.S. press’s prisms for viewing and interpreting the post-Communist world.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMTYzNDQzNzEzNDk1MDc3